Calcite Dissolution by Brevibacterium sp. SOTI06: A Futuristic Approach for the Reclamation of Calcareous Sodic Soils - Tamilselvi, S. M.; Thiyagarajan, Chitdeshwari; Uthandi, Sivakumar (Frontiers in Plant Science, 2016)
Assessing the ability of soil microorganisms to dissolute poorly soluble native calcite to supply Ca2+ is a new area to be explored in reclaiming sodic soils by supplying adequate Ca2+ and reducing the recurrent sodicity. Hence, the present study aimed to isolate a calcite dissolving bacteria (CDB) from calcareous sodic soils and to understand the mechanism of calcite dissolution. Of the thirty three CDB isolates recovered from the calcareous sodic soils of Tamil Nadu (Coimbatore, Ramnad and Trichy), eleven isolates were screened for calcite dissolution based on titratable acidity. 16S rRNA gene sequence analysis of the three best isolates viz., SORI09, SOTI05 and SOTI06 revealed 99 % similarity to Bacillus aryabhattai, 100 % to B. megaterium and 93 % to Brevibacterium sp., respectively. Among them, Brevibacterium sp. SOTI06 released more Ca2+ (3.6 g.l-1) by dissolving 18.6 % of the native calcite. The spectral data of FTIR also showed reduction in the intensity of calcite (55.36 to 41.27) by the isolate at a wave number of 1636 cm-1 which confirmed the dissolution. Besides producing organic acids (gluconic acid and acetic acid), Brevibacterium sp. SOTI06 also produced siderophore (91.6 %) and extracellular polysaccharides (EPS, 13.3 µg. ml-1) which might have enhanced the calcite dissolution.